Training and onboarding initiatives in high energy physics experiments - Reinsvold Hall, Allison; Skidmore, Nicole; Benelli, Gabriele; Carlson, Ben; David, Claire; Davies, Jonathan; Deconinck, Wouter; DeMuth, David; Elmer, Peter; Garg, Rocky Bala; Hageböck, Stephan; Lieret, Killian; et al. (Frontiers in Big Data, 2025)
In this article we document the current analysis software training and onboarding activities in several High Energy Physics (HEP) experiments: ATLAS, CMS, LHCb, Belle II and DUNE. Fast and efficient onboarding of new collaboration members is increasingly important for HEP experiments. With rapidly increasing data volumes and larger collaborations the analyses and consequently, the related software, become ever more complex. This necessitates structured onboarding and training. Recognizing this, a meeting series was held by the HEP Software Foundation (HSF) in 2022 for experiments to showcase their initiatives. Here we document and analyze these in an attempt to determine a set of key considerations for future HEP experiments.